2021
DOI: 10.1371/journal.pone.0260989
|View full text |Cite|
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 antibodies and retrospective mortality in a refugee camp, Dagahaley, Kenya

Abstract: Background Camps of forcibly displaced populations are considered to be at risk of large COVID-19 outbreaks. Low screening rates and limited surveillance led us to conduct a study in Dagahaley camp, located in the Dadaab refugee complex in Kenya to estimate SARS-COV-2 seroprevalence and, mortality and to identify changes in access to care during the pandemic. Methods To estimate seroprevalence, a cross-sectional survey was conducted among a sample of individuals (n = 587) seeking care at the two main health … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Additionally, like in other surveys [ 9 , 10 , 14 , 15 , 23 ], seroprevalence increased with age categories and was significantly higher among adults aged >40 years, with a seroprevalence of 84% in both countries for this age group compared to a seroprevalence of <70% among youth aged <19 years. Our previous surveys [ 9 ] showed that in Cameroon, seroprevalence was 13.1% (95% CI, 9.3%–18.3%) in the younger age group (<19 years) and 22.9% (95% CI, 17.5%–29.2%) in the older age group (>40 years) at the time of the first survey just before the start of the second wave of COVID-19.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Additionally, like in other surveys [ 9 , 10 , 14 , 15 , 23 ], seroprevalence increased with age categories and was significantly higher among adults aged >40 years, with a seroprevalence of 84% in both countries for this age group compared to a seroprevalence of <70% among youth aged <19 years. Our previous surveys [ 9 ] showed that in Cameroon, seroprevalence was 13.1% (95% CI, 9.3%–18.3%) in the younger age group (<19 years) and 22.9% (95% CI, 17.5%–29.2%) in the older age group (>40 years) at the time of the first survey just before the start of the second wave of COVID-19.…”
Section: Discussionsupporting
confidence: 80%
“…Between the first and third surveys, done just before and after the second wave, respectively, seroprevalence increased from 18.9% (95% CI, 12.1%–28.4%) to 35.5% (95% CI, 31.3%–39.8%) among those <19 years of age and from 22.6% (95% CI, 16.3%–30.6%) to 58.9% (95% CI, 52.6%–64.9%) among those >40 years of age. As reported in these studies and in most seroprevalence studies conducted in Africa, seroprevalence was significantly associated with age [ 9 , 10 , 14 , 15 , 23 ].…”
Section: Discussionmentioning
confidence: 52%
“…One qualitative study reported on the impact of COVID-19 on utilization and access to maternal services among eleven refugee women in urban Kenya [ 16 ]. Another article estimated the mortality rate and seroprevalence of SARS-CoV-2 antibodies among residents in a refugee camp in Kenya as well as compared consultations at health centers before and during the pandemic [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent cross-sectional study performed in the Dagahaley refugee camp in Kenya, the seroprevalence of SARS-CoV-2 antibodies was estimated among individuals (n = 587) who were seeking care and among all household members (n = 619) of the community of health workers working in the camp. 13 In this study, the number of infected people was estimated to be 67 times higher outside the camps than the number of reported cases, and the individuals over 50 years of age were particularly vulnerable. Among the refugees, an additional health issue was mental health problems associated with the COVID-19 pandemic.…”
Section: Refugees and Covid-19mentioning
confidence: 69%